Pengaruh Pemahaman Investasi Terhadap Minat Mahasiswa Berinvestasi Di Pasar Modal - Dewi Agustin; Shelli Yuniar; Eleazar Luna Azzura; Dedi Mulyadi; Dwi Epty (Jurnal Mirai Management, 2022)
Market capital is used as a meeting place for individuals or entities who want to channel their funds to invest in the capital market, while capital companies will develop so that they can expand their reach. The purpose of this study is to find out whether there is a relationship between investment understanding and investment interest among students. The method used is simple linear regression with student respondents. The results of this study indicate that there is an influence of investment understanding on investment interest among students. This can be seen from the regression equation Y = 3.673 + 0.823X where the value of t count > t table or 14.529 > 1.984, so that it can be interpreted that there is a significant influence between investment understanding on students' interest in investing in the capital market. Keywords: Interests, Investments, Capital Markets